5-HT6 Receptors Sex-Dependently Modulate Hippocampal Synaptic Activity through GABA Inhibition - Caroline Lahogue; Jean-Marie Billard; Thomas Freret; Valentine Bouet (Biomolecules, 2023)
The subtype 6 of the serotoninergic receptors (5-HT6Rs) is highly expressed in the hippocampus, and evidence indicates the beneficial effects of 5-HT6Rs blockade on short- and long-term memory in rodents. Nevertheless, the underlying functional mechanisms still need to be established. To this end, we performed electrophysiological extracellular recordings to assess the effects of the 5-HT6Rs antagonist SB-271046 on the synaptic activity and functional plasticity at the CA3/CA1 hippocampal connections of male and female mice slices. We found that basal excitatory synaptic transmission and isolated N-methyl-D-aspartate receptors (NMDARs) activation were significantly increased by SB-271046. The NMDARs-related improvement was prevented by the GABAAR antagonist bicuculline in male but not in female mice. Regarding synaptic plasticity, neither paired-pulse facilitation (PPF) nor NMDARs-dependent long-term potentiation (LTP) (induced either by high-frequency or theta-burst stimulation) was affected by the 5-HT6Rs blockade. Taken together, our results indicate a sex-dependent 5-HT6Rs effect on synaptic activity at the CA3/CA1 hippocampal connections through changes in the excitation/inhibition balance.